Relationship between language competency and business opportunity - Soon, Chiow Thai; Mohd. Sohaimi Esa; Siti Nurul Aishah Abdul Hamid; Henry Bating (Global Academic Excellence, 2021)
The article reviewed the relationship between language competency and business opportunity in five global regional trading blocs. By having the language competency may facilitate the business opportunity but language differences may create frictions between the business partners and/or the workers. Besides for the purpose of communication, language use in the business world may enhance trust and loyalty between business partners and from the customers. Different linguistic landscapes are formed and dominated by different language communities in the global business world. Five important languages used in the global business world which are English, Mandarin, Spanish, German and Portuguese, are reviewed according to their regional trading blocs. Malaysian authority specifically the Malaysian Education Ministry is suggested to design and adapt more practical and relevant education language plan to produce graduates with different language competencies for the future human resource market. The authority is also suggested to create a favourable institutional environment for variant language use in the country.